Orbiting Jupiter - Schmidt, Gary D. (Clarion Books, Houghton Mifflin Harcourt, 2015)
"Jack, 12, tells the gripping story of Joseph, 14, who joins his family as a foster child. Damaged in prison, Joseph wants nothing more than to find his baby daughter, Jupiter, whom he has never seen. When Joseph has begun to believe he'll have a future, he is confronted by demons from his past that force a tragic sacrifice"--Provided by publisher.